Seeking Reconciliation : The Peacemaking Witness of the Church in Malaysia - Rowan, Peter (Book collections on Project MUSE., 2019)
This is an abridged version of Peter Rowan's Regnum book, Proclaiming the Peacemaker. With a history of racial violence and in recent years, low-level ethnic tensions, the themes of peaceful coexistence and social harmony are recurring ones in the discourse of Malaysian society. In such a context, this book looks at the role of the church as a reconciling agent, arguing that a reconciling presence within a divided society necessitates an ethos of peacemaking. Such an ethos is created and sustained when Christians understand that their identity has been transformed in Jesus Christ. With a combi.